The ECO-FERMENTASI DAN APLIKASINYA PADA LAHAN MARGINAL DI DESA REULEUT BARAT ACEH UTARA - Nilahayati; Rosnina Abdul Gani; Zurrahmi Wirda; Dewi Sartika A (Global Science Society, 2022)
ABSTRACT Reuleut Barat is a village assisted by Malikussaleh University which is classified Inceptisol soil as sub-optimal land that has a low pH and comes from low of organic matter. The low quality of land in the West Reuleut area as marginal land that is less productive has an impact on the low income and welfare of its people. The limitations of productive land can be overcome by the application of biotechnology innovations by utilizing microorganisms through the application of organic fertilizers. Organic fertilizers can be obtained from a waste processing process known as the 3R (reuse, reduce and recycle). Making eco-fermentation is done by sorting household waste as an initial step in producing organic fertilizer by processing vegetable waste materials such as fruit peels such as papaya, pineapple, oranges which are added with molasses as an activator of microorganisms in the fermentation process so that the final product obtained is a liquid that is easy to use in its application to the ground. The application of Eco-fermentation fertilizers as organic materials containing microflora has a role in increasing the activity of marginal soil microorganisms into productive land through the weathering process of soil organic matter which can improve the physical, chemical, and biological properties of the soil so that ultimately it can increase soil fertility which can increase crop production of Reuleut Barat village. Keywords: eco-fermentation, sub-optimal land, organic-waste